IDIOPATHIC FASCICULAR LEFT VENTRICULAR TACHYCARDIA: A DIAGNOSTIC CHALLENGE - Chang, Chee Yik (Journal of Ayub Medical College Abbottabad, 2021)
A 28-year-old female, with no prior medical illness presented with intermittent palpitation for 1 week duration. She denied dyspnoea, chest pain, syncope or symptoms of hyperthyroidism. She reported no family history of heart disease or sudden cardiac death. Upon presentation, her blood pressure was 100/69 mmHg and heart rate was 137 beats per minute. Clinically, there were no signs of anaemia, heart failure, or valvular abnormality. The blood investigations including serum electrolytes and thyroid function test were within the normal limits and transthoracic echocardiography revealed a structurally normal heart. The ECG showed narrow complex ventricular tachycardia with atrioventricular dissociation, left axis deviation (LAD) and right bundle branch block (RBBB) (Figure 1a). However, it was initially misinterpreted as atrial fibrillation with rapid ventricular response. As a result, beta-blocker, digoxin, and amiodarone were given sequentially as an attempt to terminate the arrhythmia, but to no avail. Finally, the diagnosis was revised to idiopathic fascicular left ventricular tachycardia (IFLVT) in view of the ECG findings. Intravenous verapamil was administered and the arrhythmia was successfully terminated with verapamil 7.5 mg (Figure 1b). She was started on maintenance oral verapamil while waiting for catheter ablation at a later date.